APPLICATION OF PROVISIONS ARTICLE 127 JO ARTICLE 103 LAW NUMBER 35 OF 2009 CONCERNING NARCOTICS IN LAW ENFORCEMENT NARCOTICS MISUSE (Study of Several District Court Decisions) - Syamsuir Syamsuir; Marlina Marlina; Adil Akhyar (LPPM YPITI, 2021)
The substance of the Narcotics Act has not provided a clear conception regarding the application of the law to narcotics users who use narcotics for themselves who are qualified as addicts and narcotics victims. As a result, the application of the law against narcotics users, has not yet fully realized legal certainty. dapun problems in this study regarding the application of Article 127 in conjunction with Article 103 of the Narcotics Act? Regarding the obstacles in applying the provisions of Article 127 in conjunction with Article 103 of the Narcotics Act against narcotics abusers? What is the ideal criminal law policy in making effective the implementation of Article 127 in conjunction with Article 103 of the Narcotics Act?This type of research is normative juridical research, while the nature of the study is descriptive analysis. This research uses several approaches, namely the law and conceptual approach. The research data consisted of secondary data sources. The data analysis used in this study is qualitative data analysis. Based on the results of the study, the application of Article 127 in conjunction with Article 103 of the Narcotics Act against abusers who use narcotics for themselves does not yet have legal certainty. The substance of the Narcotics Act is still ambiguous. Obstacles in applying the provisions of Article 127 in conjunction with Article 103 of the Narcotics Act, are influenced by three factors, namely the legal substance factor that has not been supported. Legal structure factors, related to the not yet created professionalism of law enforcement officers in law enforcement and legal cultural factors, that is related to community legal awareness. The ideal criminal law policy in streamlining the application of Article 127 in conjunction with Article 103 is to revise the provisions of the Narcotics Act, specifically Article 112 Paragraph (1) of the Narcotics Act by adding the phrase